Publisher Correction: Revisiting the gut–joint axis: links between gut inflammation and spondyloarthritis (Nature Reviews Rheumatology, (2020), 16, 8, (415-433), 10.1038/s41584-020-0454-9) - Gracey, Eric; Vereecke, Lars; McGovern, Dermot; Fröhling, Mareike; Schett, Georg; Danese, Silvio; De Vos, Martine; Van den Bosch, Filip; Elewaut, Dirk (Nature Reviews Rheumatology, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.
CRIS-Team Scopus Importer:2020-08-07